Managing Qur'an Memorization Learning through the Tasmi' Method: An Indonesian Islamic Boarding School - Nurdalia Nurdalia; Taufiqurrahman Taufiqurrahman (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Although tasmi’ the practice of aloud Quranic recitation for verification is widely utilized across Indonesian tahfidz (memorization) institutions, its specific internal management mechanisms remain underdocumented in empirical literature. This qualitative case study examines the management, implementation, and overall effectiveness of the tasmi’ method at the As'adiyah Central Mosque Tahfidz Institution in Sengkang, Indonesia. Data was gathered through semi-structured interviews with seven purposively selected informants, including the head, deputy head, instructors, and students, alongside non-participant observations and extensive document reviews. Data analysis followed an interactive model of condensation, display, and conclusion drawing, with credibility established via source and method triangulation. The findings reveal a highly structured management sequence: specialized tajwīd coaching, daily memorization deposits, forty-one repetitions of a completed juz’ known as maddarasa patappulo seddi, and a public, livestreamed tasmi’ session. Supported by a rigorous five-juz’ certification scheme, this framework significantly strengthens recitation fluency, tajwīd accuracy, long-term retention (mutqin), student discipline, and self-confidence while systematically reducing performance anxiety. This study conceptualizes tasmi’ as a dual-function instrument serving both formative evaluation and character development. Moreover, it reframes the local maddarasa patappulo seddi tradition as an indigenous application of modern retrieval-practice and spaced-repetition principles, offering a highly transferable institutional model. Ultimately, these insights assist global tahfidz institutions aiming to optimize memorization quality through structured, community-witnessed oral examinations within Islamic educational management frameworks.